Hematological abnormalities and associated factors among patients with thyroid hormone dysfunction at the University of Gondar Comprehensive Specialized Hospital, Northwest Ethiopia - Befikad Mandefro; Amanuel Kelem; Zenebe Abebe Gebreegziabher; Yemataw Gelaw; Elias Shiferaw; Tiruneh Adane (PLoS ONE, 2025)
Background Thyroid hormones substantially influence the metabolism and production of blood cells; as a result, blood disorders are frequently seen among patients with thyroid hormone disorders. Therefore, this study aimed to assess hematological abnormalities and associated factors among patients with thyroid hormone dysfunction. Methods A hospital-based cross-sectional study was conducted from March 12/03/2022 to May 26/05/2022 among consecutive selected 308 study participants at the University Gondar Comprehensive Specialized Hospital, Northwest Ethiopia. A structured questionnaire and data extraction sheet were used to collect socio-demographic and Clinical data, respectively. For complete blood cell count analysis venous blood was collected and analyzed by Beckman-coulter DXH-800 hematology analyzer. Data was entered by Epi data version 3.1 and analyzed by Stata version 14. Binary and multivariable logistic regressions were done to identify associated factors of hematological abnormality. A P-value less than 0.05 was considered statistically significant. Results The overall magnitude of anemia, leukopenia, thrombocytopenia, thrombocytosis, leukocytosis, and polycythemia was 26.3%, 5.5%, 2.6%, 2.3%, 2.3%, and 1.3%, respectively. Hypothyroidism (AOR = 2, 95% CI:1.0–3.6), alcohol consumption (AOR = 4, 95% CI: 1.7–9.2), meat consumption (AOR = 4, 95% CI: 1.6–10.4), vegetable consumption (AOR = 2.5, 95% CI:1.1–5.5) and febrile illness (AOR = 2.6, 95% CI:1.3–5.4) were found to be associated with anemia. Conclusion Anemia was a moderate public health problem among thyroid dysfunction patients, mainly normocytic normochromic anemia was the most common type of anemia, leukopenia was second major hematological abnormality. Hypothyroidism, alcohol consumption, meat consumption, vegetable consumption, and febrile illness were associated with anemia. Thus, all patients with thyroid dysfunction should have regular anemia screenings, particularly those with important risk factors. This could aid in the early identification and efficient treatment of anemia, improving the patients’ quality of life.